2012
DOI: 10.1186/1550-2783-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake and stress fractures among elite male combat recruits

Abstract: BackgroundAppropriate and sufficient dietary intake is one of the main requirements for maintaining fitness and health. Inadequate energy intake may have a negative impact on physical performance which may result in injuries among physically active populations. The purpose of this research was to evaluate a possible relationship between dietary intake and stress fracture occurrence among combat recruits during basic training (BT).MethodsData was collected from 74 combat recruits (18.2 ± 0.6 yrs) in the Israeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 34 publications
5
66
1
5
Order By: Relevance
“…The incidence of stress fracture (7%) was similar to that previously reported for this military population [3]. But this incidence was higher than that reported for male recruits in other military training programmes [6,8,10,15], aside from the Israeli Forces [26,27]. …”
Section: Main Findingssupporting
confidence: 76%
“…The incidence of stress fracture (7%) was similar to that previously reported for this military population [3]. But this incidence was higher than that reported for male recruits in other military training programmes [6,8,10,15], aside from the Israeli Forces [26,27]. …”
Section: Main Findingssupporting
confidence: 76%
“…In short, optimal nutrition can reduce fatigue and injuries, promote recovery from injuries [17,18], optimize the human body’s energy stores, and directly influence athletes’ health status [19,20]. Athletes and their teams strive for the best and most convenient nutritional practices to suit the individual needs of each athlete.…”
Section: Introductionmentioning
confidence: 99%
“…D, as well as other parameters related to low vit. D levels such as elevated serum PTH concentration and decreased BMD, have been implicated [4044]. …”
Section: Vitamin D and Stress Fracturesmentioning
confidence: 99%
“…A recent study found that the development of stress fractures during basic training was associated with dietary deficiency of mainly vitamin D and calcium before induction and during basic training [44]. …”
Section: Vitamin D and Stress Fracturesmentioning
confidence: 99%